An Exploration of Resilience and Positive Affect among Undergraduate Nursing Students: A Longitudinal Observational Study. - Mayor-Silva, L. Iván; Meneses-Monroy, Alfonso; Rodriguez-Leal, Leyre; Moreno, Guillermo (Nursing Reports, 2024)
Background: The purpose of this study is to analyze the variation in resilience and emotional state scores in nursing students throughout the four years of training for the nursing degree. Methods: This is a longitudinal observational study of a paired and prospective cohort of 176 nursing students who enrolled in the first year of a bachelor's degree in 2019. The study followed up with the students in 2022 and examined several sociodemographic factors, including sex, marital status, date of birth, living arrangements and occupation. Additionally, the study investigated changes in negative affect, positive affect, and resilience. Results: A total of 176 students participated in the study. The study found that resilience increased from 68.24 ± 10.59 to 70.87 ± 9.06 (p < 0.001), positive affect increased from 28.16 ± 4.59 to 33.08 ± 8.00 (p < 0.001), and the negative affect score decreased from 25.27 ± 5.12 to 21.81 ± 7.85 (p < 0.001). The study also found that married individuals experienced an increase in negative affect (p = 0.03) compared to singles or those in open relationships. Furthermore, the change in resilience was greater in men than in women (p = 0.01). Conclusions: Throughout their four-year training, nursing students experience an increase in resilience and positive affect, as well as a decrease in negative affect.